Impact of Insolvency and Bankruptcy Code on Insolvency Resolution (Journal of Informatics Education and Research, 2025)
The Insolvency and Bankruptcy Code was enacted from 2016 and marks a complete shift in corporate insolvency resolution processes in India. The idea was to assume that an arrangement in the company survives so that the best interest of all stakeholders was served rather than the liquidation of the company itself. Liquidation may be a suitable option in some cases, if the business is viable and has the potential for revival, ensuring the survival of the company becomes the preferred goal. This vision is reflected in the preamble of the IBC1: